Seasonal variation of VO2max and the VO2-work rate relationship in elite alpine skiers - Gross, M. A.; Breil, F. A.; Lehmann, A. D.; Hoppeler, H.; Vogt, M. (Medicine & Science in Sports & Exercise, 2009)
Purpose: Alpine ski performance relates closely to both anaerobic and aerobic capacities. During their competitive season, skiers greatly reduce endurance and weight training, and on-snow training becomes predominant. To typify this shift, we compared exhaustive ramp cycling and squat (SJ) and countermovement jumping (CMJ) performance in elite males before and after their competitive season.